2023
DOI: 10.1002/advs.202300471
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Sensor Reservoir Computing for Gait Recognition via a Multi‐Gate Electrolyte‐Gated Transistor

Abstract: The recent emergence of various smart wearable electronics has furnished the rapid development of human-computer interaction, medical health monitoring technologies, etc. Unfortunately, processing redundant motion and physiological data acquired by multiple wearable sensors using conventional off-site digital computers typically result in serious latency and energy consumption problems. In this work, a multi-gate electrolyte-gated transistor (EGT)-based reservoir device for efficient multi-channel near-sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The rise and decay of the channel currents reflect the temporal characteristics of the optical pulse stimulation, which is indicative of the device’s high suitability for RC (Supplementary Fig. 7 ) 34 . Furthermore, the response under blue light (450 nm) illumination was investigated, and a similar volatile behavior as that under low-intensity UV illumination was observed, but with a much smaller magnitude of change (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The rise and decay of the channel currents reflect the temporal characteristics of the optical pulse stimulation, which is indicative of the device’s high suitability for RC (Supplementary Fig. 7 ) 34 . Furthermore, the response under blue light (450 nm) illumination was investigated, and a similar volatile behavior as that under low-intensity UV illumination was observed, but with a much smaller magnitude of change (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Electrolyte-gated transistors (EGT), with tunable ion dynamic timescales at different gate voltages, show great potential for processing dynamic information in a single device 33 , 34 . Our previous study demonstrated that the reconfigurable property derives from the electric double layer (EDL) and the ion migration mechanisms 35 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, reservoir computing (RC) has emerged as a promising algorithm for processing temporal data. In the RC, temporal signals are transformed into high-dimensional states, enabling complex inputs to become linearly separable on the basis of reservoir states. This transformation of inputs enables efficient processing through a simple readout layer, resulting in significant reductions in network scale and training cost. , Recently, several physical reservoirs have been proposed, including those utilizing metal oxides, ,, two-dimensional materials, and organics. The effectiveness of the RC system, which is characterized by fading memory and distinct reservoir states, has been successfully demonstrated in these studies. Nonetheless, only a few of these reservoirs possess the combined features of light responsiveness, CMOS compatibility, and scalability.…”
Section: Introductionmentioning
confidence: 99%
“…Various physical reservoirs have been used in the reservoir layer, [11][12][13][14][15][16][17] and research into materials-based reservoir computing is currently accelerating. [18][19][20] For example, reservoir computing research exists using atomic switch technologies to control the growth and contraction of Ag filaments from Ag 2 S. 12,21,22) Ag 2 S reservoirs have also been used for benchmarking tasks such as STM, PC, and MNIST image recognition and optical pattern classification. 23,24) In terms of social implementation of artificial intelligence, AI robot development using machine learning, such as deep learning, has been conducted in recent years, [25][26][27] which will meet the increasing demand for care and assistance robots.…”
Section: Introductionmentioning
confidence: 99%